Expression and Function of the Endocannabinoid Modulating Enzymes Fatty Acid Amide Hydrolase and N-Acylphosphatidylethanolamine-Specific Phospholipase D in Endometrial Carcinoma - Ayakannu, Thangesweran; Taylor, Anthony H.; Bari, Monica; Mastrangelo, Nicoletta; Maccarrone, Mauro; Konje, Justin C. (Frontiers in Oncology, 2019)
Background: The concentrations of three N-acylethanolamines (NAEs), anandamide (AEA), N-oleoylethanolamide (OEA) and N-palmitylethanolamide (PEA) are increased in the endometria of women with endometrial cancer (EC). It is widely accepted that plasma levels of these three NAEs are regulated by the actions of the N-acylphoshatidylethanolamine-specific phospholipase D (NAPE-PLD) and fatty acid amide hydrolase (FAAH), enzymes that are, respectively, rate-limiting synthesis and degradative. The expression and activity of these enzymes has not previously been studied in EC. Methods: FAAH activity in peripheral blood lymphocytes, and transcript and protein expression for FAAH and NAPE-PLD in EC tissues were measured using enzyme, quantitative RT-PCR and histomorphometric analyses of immunoreactive tissue sections, respectively. Samples were provided by 6 postmenopausal women (controls) and 34 women with histologically diagnosed EC. Results: Peripheral lymphocyte FAAH activity was unaffected in women with EC when compared with women devoid of disease. The FAAH transcript expression level was 75% lower in EC whilst NAPE-PLD levels were non-significantly increased. A significant tumour type-dependent 70-90% decrease in FAAH protein and significant 4- to 14-fold increase in NAPE-PLD protein was observed in the malignant tissue that correlated with advancing disease, complementing the transcript data. Correlation analyses also confirmed that increased tissue NAE concentrations were inversely related to FAAH expression and directly correlated to NAPE-PLD expression and the NAPE-PLD/FAAH ratio. Conclusion: These data support the previously observed tissue levels of AEA, OEA and PEA and a role for NAE metabolism in the pathogenesis of EC.